Antipsychotic polypharmacy in the treatment of schizophrenia in China and Japan. (December 2018) - Qiu, Hong; He, Yong; Zhang, Yongjing; He, Minfu; Liu, Jin; Chi, Rui; Si, Tianmei; Wang, Huaning; Dong, Wentian
Background: Although antipsychotic monotherapy is recommended as the main treatment for schizophrenia, antipsychotic polypharmacy is not rare in practice. However, longitudinal data on antipsychotic polypharmacy in schizophrenia treatment are limited. Methods: This longitudinal database study described antipsychotic polypharmacy in the treatment of schizophrenia in real-world settings in China and Japan. We retrieved information about antipsychotic treatment for schizophrenia from January 2010 to December 2014 from two hospital Electronic Medical Records databases in China and one claims database, Japan Medical Data Centre in Japan. Eligible patients had a diagnosis of schizophrenia (International Classification of Diseases, Tenth Revision F20.x) and at least one prescription for first or second generation antipsychotics. Antipsychotic polypharmacy was defined as having more than one antipsychotic medication overlapping for ⩾60 days. The Japan Medical Data Centre study cohort was further stratified by employees (insurance beneficiaries) and their dependents. Results: The study cohorts comprised 11, 961 patients from China and 25, 034 (10, 661 employee sub-cohort and 14, 373 dependent sub-cohort) from 14 days Japan Medical Data Centre in Japan. Most patients were prescribed monotherapy (87.3% in China and 80.1% in Japan), of which oral second-generation antipsychotics were the majority (78.9% in China and 65.8% in Japan). The prevalence rate of antipsychotic polypharmacy was 12.7% in China and 19.9% in Japan (13.7% in employees vs 24.5% in dependents). The most common combinations were two oral antipsychotics. Combinations of more than two drugs were uncommon in China (0.3%) but were prescribed for 5.3% of patients in Japan. Among patients treated with monotherapy, 12.6/100 person-years (11.8%) in China and 9.6/100 person-years (11.0%) in Japan switched to antipsychotic polypharmacy during follow-up. Younger patients were more likely to switch to antipsychotic polypharmacy than older patents in all study cohorts. Conclusion: The observed rates of antipsychotic polypharmacy ranged from 12.7% in China to 19.9% in Japan. Switching from monotherapy to antipsychotic polypharmacy was most likely to occur in younger patients with schizophrenia.